2019
DOI: 10.3390/app9204336
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Seismic Performance of Recycled Concrete Hollow Block Masonry Walls

Abstract: This paper aims to manufacture recycled concrete hollow block (RCHB) which can be used for the masonry structure with seismic requirements. Five RCHB masonry walls were tested under cyclic loading to evaluate the effect of the axial compression stress, aspect ratio, and the materials of structural columns on the seismic performance. Based on the test results, the failure pattern, hysteresis curves, lateral drift, ductility, stiffness degradation, and the energy dissipation of the specimens were analyzed in det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…It could also be observed that the compressive stress could increase the shift angle of the specimens. Similar conclusions were also provided by Liu et al [31].…”
supporting
confidence: 91%
See 3 more Smart Citations
“…It could also be observed that the compressive stress could increase the shift angle of the specimens. Similar conclusions were also provided by Liu et al [31].…”
supporting
confidence: 91%
“…It could be concluded that the secant stiffness at different characteristic states increased with the decrease of aspect ratio and increase of compressive stress. e stiffness degradation and secant stiffness of the specimens are similar to those provided in the literature [31].…”
Section: Stiffness Degradationsupporting
confidence: 79%
See 2 more Smart Citations
“…Several studies have been carried out to understand the seismic performance of URM and cement-based structures using dynamic tests. These investigations include cyclic loading of walls and structures using actuators [8,9] and shaking table testing [10,11]. In many cases, researchers have utilized scaled models for the dynamic testing of masonry structures [12,13] since the testing of full-scale models could be costly or infeasible.…”
Section: Introductionmentioning
confidence: 99%